I, robot - Asimov, Isaac, 1920-; Beltrami, Marco; Cromwell, James; Duggan, Simon, 1959-; Greenwood, Bruce, 1956-; Mark, Laurence; Moynahan, Bridget, 1972-; Proyas, Alex, 1963-; Smith, Will, 1968-; Tudyk, Alan.; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, CA : 20th Century Fox Home Entertainment, 2004)
Un detective investiga el asesinato de un destacado científico, quien cree que fue asesinado por uno de los robots que el científico creó.
Based on the idea suggesed in a book by Isaac Asimov.
Material extra: commentary by director Alex Proyas and screenwriter Akiva Goldsman; the making-of 'I, robot'; still gallery; Fox's inside look: Mr. and Mrs. Smith, robots, and Elektra.
Título del envase.
Director of photography, Simon Duggan ; art directors, Chris August, Helen Jarvis ; editors, Shawn Broes, William Hoy, Richard Learoyd, Armen Minasian ; music, Marco Beltrami ; costume designers, Liz Keogh, Elizabeth Keogh Palmer ; production designer, Patrick Tatopoulos ; visual effects supervisor, John Nelson ; special effects director, Mike Vezina.
Will Smith, Bridget Moynahan, Alan Tudyk, James Cromwell, Bruce Greenwood, Adrian Ricard, Chi McBride, Jerry Wasserman, Fiona Hogan.
MPAA rating: PG-13; for intense stylized action, and some brief partial nudity.
Keywords: Películas cinematográficas; Robots -- Teatro